2008
DOI: 10.1007/s00520-008-0510-5
|View full text |Cite
|
Sign up to set email alerts
|

Palonosetron (Aloxi®) and dexamethasone for the prevention of acute and delayed nausea and vomiting in patients receiving multiple-day chemotherapy

Abstract: The present results appear to be encouraging in terms of complete prophylaxis of CINV and treatment of breakthrough emesis in the setting of multiple-day chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 31 publications
0
35
2
Order By: Relevance
“…A single 0.25 mg dose, repeatable after 72 h, proved effective in patients receiving multiple-day chemotherapy. 6 Headache was its most common side effect. 5 Palonosetron prevented nausea and vomiting in 36% of patients undergoing autologous BMT, whereas in another 26% symptom control was achieved following a second dose.…”
mentioning
confidence: 99%
“…A single 0.25 mg dose, repeatable after 72 h, proved effective in patients receiving multiple-day chemotherapy. 6 Headache was its most common side effect. 5 Palonosetron prevented nausea and vomiting in 36% of patients undergoing autologous BMT, whereas in another 26% symptom control was achieved following a second dose.…”
mentioning
confidence: 99%
“…29 Moreover, we planned a prophylaxis regimen with short and low-dose dexamethasone and only one administration of palonosetron, with a second administration reserved only for breakthrough emesis treatment, which rescued 67% of the patients. The only treatment-related adverse events associated were transient constipation or mild and transient headache.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] The second-generation 5-HT 3 RA, namely palonosetron, and the neurokinin receptor antagonist, aprepitant, have improved not only the prevention of acute CINV, but also the prophylaxis of delayed CINV [13][14][15][16][17][18][19] after both moderately and highly emetogenic CT. However, control of delayed CINV is still an open problem, especially in patients undergoing multiple-day [20][21][22][23] or high-dose (HD)-CT. [24][25][26][27] Two recent studies 28,29 have shown the efficacy and safety of palonosetron plus dexamethasone in preventing CINV during and after multiple-day CT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be treated with 5-Hydroxytryptamine 3 (5-HT3) antagonists like dolasetron, granisetron, ondansetron and Neurokinin 1 (NK1) receptor antagonists like fosaprepitant and aprepitant. 9 Cancer patient are mainly affected by the progressive cachexia, and is one among the major causes where it presents as progressive weight loss, anorexia, and persistent erosion of host body cell mass in response to a malignant growth. 10 Deficiency of any of the micronutrients needs to be corrected by administering drugs like iron, folic acid and multivitamins.…”
Section: Introductionmentioning
confidence: 99%